2011
DOI: 10.1021/om101060n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Osmium η5-Phospholide Complexes and Their Reactions with Acyl Electrophiles: C═O Bond Cleavage and C−C Bond Formation within the Metal Coordination Sphere

Abstract: Two diphosphaosmocene species have been prepared in excellent yields by the reaction of a lithium 2,5-dialkylphospholide (alkyl = cyclohexyl, (-)-menthyl) and [(η 6 -cymene)OsCl 2 ] 2 in THF. These are the first examples of phosphametallocenes with an osmium core. For the success of the phosphaosmocene synthesis, the use of a sterically demanding phospholide is crucial. A treatment of the 2,2 0 ,5,5 0 -Cy 4 -diphosphaosmocene with an AcCl/AlCl 3 mixture in dichloromethane gives a novel (μ-vinylidene)osmium com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The only weaknesses of the approach at the present time seem to lie in the sensitivity of the Cu(I) templation methodology to the nature of the incoming metal centre, so that free keto-bis-( phosphametallocene) ligands have only been obtained in cases where i): at least one of the metal centres is iron, and ii): this centre is incorporated late in the synthesis as the "second" metal centre. It is well established that the preparation of phosphaferrocenes is extremely favourable relative to other late transition phosphametallocenes containing Ru, 45 Co, 46 Os, 47 Ni, 48 Rh, 49 Ir 49 etc. centres, so this is unsurprising.…”
Section: Discussionmentioning
confidence: 99%
“…The only weaknesses of the approach at the present time seem to lie in the sensitivity of the Cu(I) templation methodology to the nature of the incoming metal centre, so that free keto-bis-( phosphametallocene) ligands have only been obtained in cases where i): at least one of the metal centres is iron, and ii): this centre is incorporated late in the synthesis as the "second" metal centre. It is well established that the preparation of phosphaferrocenes is extremely favourable relative to other late transition phosphametallocenes containing Ru, 45 Co, 46 Os, 47 Ni, 48 Rh, 49 Ir 49 etc. centres, so this is unsurprising.…”
Section: Discussionmentioning
confidence: 99%
“…Could these stabilizing factors be also applied to MPBs? If such a stabilizing factor is significant, could we realize MPBs from the isomerization of η 5 -PCp metal complexes (Scheme ) which have been synthesized previously? Our ongoing interest in aromaticity has led us to investigate these phosphorus-containing metallaaromatics. , Here we report a thorough theoretical study on the interconversion of MPBs and the η 5 -PCp metal complexes (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we recently demonstrated that certain phosphametallocenes behaved in completely different ways under forcing Friedel–Crafts acylation conditions . Reactions between Cy 4 -diphospharuthenocene or the corresponding osmocene analogue and an acyl electrophile (AcCl/AlCl 3 ) produce a μ-vinylidene species, where a vinylidene moiety bridges the Ru/Os center and the phosphorus atom.…”
Section: Introductionmentioning
confidence: 99%